Range and Consistency of Infection Outcomes Reported in Trials Conducted in Kidney Transplant Recipients: A Systematic Review. Issue 12 (22nd November 2021) - Chan, Samuel; Au, Eric; Johnson, David W.; Hawley, Carmel M.; Tong, Allison; Pascoe, Elaine M.; Craig, Jonathan C.; Sautenet, Benedicte; Blumberg, Emily A.; Brennan, Daniel; Campbell, Scott B.; Cao, Christopher; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Infection remains a leading cause of death in kidney transplant recipients. This study aimed to assess the scope and consistency of infection outcomes reported in contemporary trials conducted in kidney transplant recipients. Methods: A literature review of all randomized trials and trial protocols reporting infection outcomes in adult kidney transplant recipients was identified in the Cochrane Kidney and Transplant Specialized Register from January 2014 to July 2019. Characteristics and infection outcomes from the trials were analyzed. Results: From 102 included trials, 772 outcome measures were extracted and categorized into 216 unique measures with a median of 3.2 outcome measures per trial (range: 1–9). Measures were further grouped into 32 outcomes based on site of infection (14 outcomes) and organism (18 outcomes). The most commonly reported site-specific outcome and organism-specific outcome were systemic infection (71% trials) and cytomegalovirus infection (62% trials), respectively. Outcome metric and methods of aggregation included mean, median, proportion, proportional change, and number of patients with at least 1 episode. Across all trials, measures were assessed at 55 different time points with a range of 1–11 time points per trial. Conclusions: Infection outcomes in kidney transplant recipients were frequently reported by site and organism but varied widely in terms of outcome, metrics, method of aggregation, and time point of measurement. Establishment of core outcomes for infection based on the shared priorities of patients/caregivers and health professionals may improve the consistency, comparability, and usefulness of trial evidence Abstract :